Interleukin-6 Inhibitor Olokizumab in Hospitalized Adults with Moderate COVID-19: Results of a Single Center Observational Study - Svetlana V Topolyanskaya; Rachina S.A.; Karine A. Lytkina; Georgiy G. Melkonyan; Yulia A Savochkina (West Kazakhstan Medical Journal)
A single-center observational study was performed to evaluate the effectiveness and safety of the interleukin-6 inhibitor olokizumab in hospitalized adults with moderate COVID-19. This study enrolled 337 patients aged from 22 to 96 years old. After the administration of olokizumab, there was a significant reduction in body temperature, decrease in CRP, and an increase in the levels of blood cells. Revealed clinical improvement was seen in 69.7% of cases, 8.5% of patients showed deterioration in their condition and were transferred to the ICU, 13.6% died. Olokizumab was well tolerated except for slight elevation in live enzymes, such as aspartate transaminase and alanine transaminase.